1999
DOI: 10.1002/(sici)1098-2744(199902)24:2<108::aid-mc5>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive expression of 8-lipoxygenase in papillomas and clastogenic effects of lipoxygenase-derived arachidonic acid metabolites in keratinocytes

Abstract: The expression pattern, enzymatic activity, and products of 8-lipoxygenase (LOX) were analyzed in normal and neoplastic skin of NMRI mice. While barely detectable in normal epidermis, 8-LOX was transiently induced by 12-O-tetradecanoylphorbol-13-acetate and constitutively expressed in papillomas but not carcinomas obtained by the initiation-promotion protocol of mouse skin carcinogenesis. The product profile and chirality of both the native and the recombinant protein produced the S enantiomers of 8-hydroxy-5Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
24
1
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 35 publications
1
24
1
1
Order By: Relevance
“…It is a murine homolog of human 15S-LOX-2 and metabolizes AA and LA to 8-HETE and 9-HODE, respectively (Gschwendt et al, 1986;Fu¨rsten-berger et al, 1991;Jisaka et al, 1997;Bu¨rger et al, 1999). However, it uses AA as a preferred substrate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a murine homolog of human 15S-LOX-2 and metabolizes AA and LA to 8-HETE and 9-HODE, respectively (Gschwendt et al, 1986;Fu¨rsten-berger et al, 1991;Jisaka et al, 1997;Bu¨rger et al, 1999). However, it uses AA as a preferred substrate.…”
Section: Introductionmentioning
confidence: 99%
“…In normal mouse skin, the level of 8S-LOX expression as well as 8-HETE is nearly undetectable. However, the level is highly elevated after a single topical treatment of 12-O-tetradecanoylphorbol-13-acetate (TPA) (Gschwendt et al, 1986;Fu¨rstenberger et al, 1991;Jisaka et al, 1997) and is further increased in papillomas (Bu¨rger et al, 1999;Nair et al, 2000). In carcinomas, 8S-LOX expression as well as 8-HETE production is back to the level of normal skin (Bu¨rger et al, 1999;Nair et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of 15-LOX-2 is restricted to basal keratinocytes, whereas 8-LOX was found to be expressed in suprabasal keratinocytes (14,15). 8-LOX preferentially metabolizes AA to 8-HPETE compared with LA, yielding 9-HPODE (16,17). 15-LOX-2, on the other hand, was found to accept both AA and LA as substrates to generate 15-HPETE and 13-HPODE (18).…”
mentioning
confidence: 99%
“…It metabolizes arachidonic acid as its preferred substrate and produces 8S-HETE. In addition, it was shown that 8S-LOX can convert linoleic acid to 9S-HODE, although with a much lower efficiency (14). So far constitutive enzyme expression has been detected only in mouse brain, footsole, tail, forestomach, and hair follicles (12,13,15).…”
mentioning
confidence: 99%